Increasing Contrast Improves Object Perception in Parkinson's Disease with Visual Hallucinations. Issue 1 (17th November 2020) - Díaz‐Santos, Mirella; Monge, Zachary A.; Salazar, Robert D.; Gilmore, Grover C.; Neargarder, Sandy; Cronin‐Golomb, Alice
ABSTRACT: Background: Deficits in basic vision are associated with visual hallucinations in Parkinson's disease. Of particular interest is contrast sensitivity loss in this disorder and its effect on object identification. Objectives: Evaluate whether increased contrast improves object perception in persons with Parkinson's disease and visual hallucinations, without dementia. Methods: We assessed 26 individuals with mild to moderate idiopathic Parkinson's disease, half of whom reported one or more episodes of hallucinations/unusual perceptual experiences in the past month, with a letter‐identification task that determined the contrast level required to achieve 80% accuracy. Contrast sensitivity was further assessed with a chart that presented stimuli at multiple spatial frequencies. The groups were closely matched for demographic and clinical characteristics except for experience of hallucinations. Results: Relative to participants without visual hallucinations, those with hallucinations had poorer spatial frequency contrast sensitivity and required significantly greater contrast to correctly identify the letters on the identification task. Specifically, participants with hallucinations required a mean contrast of 52.8%, whereas participants without hallucinations required 35.0%. When given sufficient contrast, the groups with and without hallucinations were equally accurate in letter identification. Conclusions: Compared to those without hallucinations, individuals with Parkinson's disease and hallucinations without dementia showed poorer contrast sensitivity. Once contrast was individually enhanced, the groups were equally accurate at object identification. These findings suggest the potential of visual perception tests to predict, and perception‐based interventions to reduce, hallucinations in Parkinson's disease.